Acthar Gel in African Americans versus Non-African Americans with Symptomatic Sarcoidosis: Physician Assessment of Patient Medical Records - Bindra J; Chopra I; Hayes K; Niewoehner J; Panaccio MP; Wan GJ (Dove Medical Press, 2024)
Jas Bindra,1 Ishveen Chopra,2 Kyle Hayes,3 John Niewoehner,3 Mary Prince Panaccio,3 George J Wan3 1Falcon Research Group, North Potomac, MD, USA; 2Manticore Consultancy, Bethesda, MD, USA; 3Mallinckrodt Pharmaceuticals, Bridgewater, NJ, USACorrespondence: George J Wan, Mallinckrodt Pharmaceuticals, 440 Route 22 East, Bridgewater, NJ, USA, Email george.wan@mnk.comIntroduction: Sarcoidosis is common among African Americans in the United States. Acthar® Gel is a viable option for the treatment of advanced symptomatic sarcoidosis. This study examined patient characteristics, Acthar Gel utilization, co-medication use, and treatment response based on physicians' assessments among African Americans versus non-African Americans with advanced symptomatic sarcoidosis.Methods: Data from the medical charts of patients were used. During data collection, patients had either completed ≥ 1 course or received treatment with Acthar Gel for ≥ 6 months.Results: This study comprised 168 African Americans and 104 non-African Americans. On average, the time since the first diagnosis of sarcoidosis was slightly longer among African Americans than non-African Americans (5.2 versus 4.3 years). Skin, heart, eyes, and joints were the most common extrapulmonary sites involved among both race groups. Shortness of breath, fatigue, bone and joint pain, and wheezing/coughing were the most frequent symptoms among both race groups. A higher proportion of African Americans versus non-African Americans were first-time Acthar Gel users and had not completed treatment during data collection. Patients in both race groups with higher starting doses of Acthar Gel therapy had a shorter treatment duration and vice-versa. A significantly lower proportion of patients among both race groups were on any co-medication after Acthar Gel initiation (p< 0.0001). Further, a higher proportion of African Americans versus non-African Americans had a reduction in any co-medication use after Acthar Gel initiation. The mean daily dose of prednisone decreased among African Americans (18.5 to 10.1 mg) and non-African Americans (17.6 to 10.0 mg) after Acthar Gel initiation. Improvement in patient health status and overall symptoms was similar for both race groups.Conclusion: Findings suggest that Acthar Gel improves health outcomes for patients with sarcoidosis, which could help to alleviate health disparities among African Americans, who are disproportionately affected by this disease.Keywords: Acthar® Gel, African Americans, medical chart review, sarcoidosis, treatment utilization, treatment response